Entropy engineering activation of UiO-66 for boosting catalytic transfer hydrogenation - Mingwei Ma; Enpeng Chen; Huijuan Yue; Ge Tian; Shouhua Feng (Nature Communications)
Abstract High-entropy metal-organic frameworks (HE-MOFs) hold promise as versatile materials, yet current rare examples are confined to low-valence elements in the fourth period, constraining their design and optimization for diverse applications. Here, a novel high-entropy, defect-rich and small-sized (32 nm) UiO-66 (ZrHfCeSnTi HE-UiO-66) has been synthesized for the first time, leveraging increased configurational entropy to achieve high tolerance to doping with diverse metal ions. The lattice distortion of HE-UiO-66 induces high exposure of metal nodes to create coordination unsaturated metal sites with a concentration of 322.4 μmol/g, which increases the abundance of Lewis acid-base sites, thereby achieving a significant improvement in the performance of the catalytic transfer hydrogenation (CTH) reaction. Systematic investigation manifests that the special electronic structure of HE-UiO-66 enhances the interaction and bonding with substrate molecules and reduces the energy barrier of the hydrogen transfer process. Our approach offers a new strategy for constructing coordination unsaturated metal sites in MOFs.